The Effect of StudentsÃ¢â‚¬â„¢ Metacognition and Digital Literacy in Virtual Lectures during the Covid-19 Pandemic on Achievement in the Ã¢â‚¬Å“Methods and Strategies on Physics LearningÃ¢â‚¬Â Course - Sukarno, S.; El Widdah, M. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
This study aims to determine the effect of studentsÃ¢â‚¬â„¢ metacognition and digital literacy skills on virtual lectures in the COVID-19 pandemic on achievement in the Ã¢â‚¬Å“Methods and Strategy on Physic Learning (MSPL)Ã¢â‚¬Â course. The data was collected using a survey method which involved all 42 physics education students. The data analysis was carried out in two stages, namely the categorization stage and the correlation stage. Based on the data and analysis, it is known that the metacognition skill of physics education students is dominated by the Ã¢â‚¬Å“highÃ¢â‚¬Â category with 40.47%, followed by the Ã¢â‚¬Å“mediumÃ¢â‚¬Â category at 35.71%, and the remaining 23.82% are at Ã¢â‚¬Å“lowÃ¢â‚¬Â category. As for the digital literacy, the variable is not much different from the metacognition skill, which is dominated by students with high category digital literacy skills at 42.85%, Ã¢â‚¬Å“moderateÃ¢â‚¬Â category at 33.33%, and the rest 23.82% are at Ã¢â‚¬Å“lowÃ¢â‚¬Â category. Likewise, in the variable conceptualization of the concept of physics and physics learning strategies, physics students who are in the Ã¢â‚¬Å“highÃ¢â‚¬Â category is more dominant than the Ã¢â‚¬Å“mediumÃ¢â‚¬Â and Ã¢â‚¬Å“lowÃ¢â‚¬Â categories, which are 33.33% and 28.58%, respectively. Based on the ANOVA table, it is known that the value of sig. 0,000, which is less than (<) 0.05. It can be said that X1 (metacognition) and X2 (digital literacy) simultaneously affect the Y variable (mastery of the MSPL concept). This is also reinforced by the calculated F value of 313.111> F table 3.22. It means that the two variables X1 and X2, simultaneously affect the Y variable (mastery of the MSPL concept).